Low-density high-strength one-step polyurethane foam as well as preparation method and application thereof
The preparation of low-density and high-strength polyurethane foam by one-step method solves the problem of poor mechanical properties of existing materials, realizes low density and high strength of the materials, simplifies the preparation process, and achieves significant performance improvement.
Patent Information
- Application Number
- CN202411628407.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
The existing low-density polyurethane foam materials have poor mechanical properties and are difficult to use as structural materials. Traditional composite reinforcement and molecular structure modification methods have problems of density increase and process complexity.
A low-density and high-strength polyurethane foam is prepared by a one-step method, and the combination of polyols, chain extenders, crosslinkers, foam stabilizers, foaming agents, free radical capture agents and catalysts and isocyanates is achieved by combining materials with specific ratios. Density and high strength.
The comprehensive mechanical properties of polyurethane foam are achieved without increasing density, with a performance improvement of about 10%, and the preparation process is simplified, suitable for automation and large-scale production.
Smart Images

Figure BDA0005135304870000051 
Figure BDA0005135304870000052 
Figure BDA0005135304870000053
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a low-density and high-strength one-step polyurethane foam and a preparation method and application thereof. Background Art
[0002] Polyurethane foam has excellent thermal insulation, sound absorption, chemical stability, energy absorption and buffering, etc., and plays an irreplaceable role in aerospace, equipment, transportation, construction and other fields. According to relevant literature (J.Appl.Polym.Sci.1998,68,1045; Plastic Foams,Part II; Marcel Dekker:New York,1973; J.Appl.Polym.Sci.2008,3,108; J.Appl.Polym.Sci.2015,74,2724-2736), the relationship between the compression strength and compression modulus of polyurethane foam materials follows the POWER law, and the logarithm of the compression strength and compression modulus is a linear function of the logarithm of the density. It can be expressed by the following formula:
[0003] log(intensity property) = log A + B log(density)
[0004] Among them, A is a constant related to the temperature and physical properties of the resin, and the correlation coefficient B is related to the properties of the foam itself, that is, the compressive strength of rigid polyurethane foam is positively correlated with its density. Low-density polyurethane foam materials have poor mechanical properties, which makes it difficult to use low-density polyurethane foam as a structural material. As aerospace vehicles, high-speed trains, submarines and other transportation vehicles continue to pursue lightweight to achieve faster speeds and better maneuverability, there is an urgent need for lightweight and high-strength polyurethane foam.
[0005] Composite reinforcement and molecular structure modification are the main ways to improve the performance of polyurethane foam. Composite reinforcement is to add glass beads, kaolin, carbon fiber, graphene, carbon nanotubes and other reinforcements to the polyurethane matrix and further prepare them into foam composite materials. Although composite reinforcement has a significant effect on improving the mechanical properties of foam materials, there are also a series of problems that are difficult to avoid. For example, the density of traditional reinforcements such as glass beads, kaolin, glass fiber, and carbon fiber is generally large, and the reinforced filler causes the foam density to increase rapidly, which is not conducive to the lightweight design of foam materials. At the same time, the reinforced filler is easy to agglomerate and difficult to disperse, which will cause defects inside the polyurethane matrix, making it difficult to further improve the mechanical strength of the foam material. Although surface treatment (coating and chemical grafting) of the reinforced filler can effectively improve its dispersibility and matrix compatibility, this method is difficult to significantly improve the mechanical strength of the foam material. At the same time, the surface treatment process is too complicated, which greatly limits its application field.
[0006] Molecular structure modification is to improve the strength of materials by changing the segment structure in the cross-linked network of polyurethane and enhancing the chemical / physical interaction in the cross-linked network. Modifying polyurethane resin with epoxy resin and phenolic resin to construct a polymer interpenetrating network is a commonly used molecular structure modification method. Rigid segments such as epoxy and phenolic resin can give the material excellent strength and modulus, and the flexible segments of polyurethane can provide good toughness for the material. This method can improve the comprehensive mechanical properties of foam without affecting the density of the foam material. However, there are differences in the reactivity of phenolic hydroxyl, alcohol hydroxyl, epoxy group and isocyanate group. In the actual process, the foaming and molding process of polyurethane foam is carried out simultaneously. The difference in reactive groups will lead to an imbalance in foaming and gelling reactions, resulting in defects such as collapse, shrinkage, and splitting, which brings challenges to the uniformity of pore structure and the stability of foam material performance. The two-step method for preparing polyurethane foam can effectively solve the problem of difference in reactive group activity, that is, first converting phenolic hydroxyl, epoxy group, etc. into alcohol hydroxyl or isocyanate group by prepolymerization and other means, and then reacting and molding when there are only alcohol hydroxyl and isocyanate groups in the reaction system. Although the two-step method can avoid the problem of reaction mismatch, the preparation process of this method is relatively long, and the viscosity of the prepolymer is relatively high, which is not conducive to subsequent uniform mixing and preparation.
[0007] In contrast, the one-step method for preparing polyurethane foam has the advantages of simple operation and high production efficiency, and is suitable for automation and large-scale production.
[0008] Therefore, it is very necessary to seek a one-step preparation method for low-density and high-strength polyurethane foam. Summary of the invention
[0009] The purpose of the present invention is to provide a low-density and high-strength one-step polyurethane foam and a preparation method and use thereof.
[0010] The invention provides a polyurethane foam, which is prepared from the following components in parts by weight: 100 parts of polyol, 5-30 parts of chain extender, 5-30 parts of crosslinking agent, 0.5-5 parts of foam stabilizer, 0.5-4 parts of blowing agent, 0.5-4 parts of free radical scavenger, 0.1-1 parts of catalyst and 150-300 parts of isocyanate.
[0011] Furthermore, the polyurethane foam is prepared from the following components in parts by weight: 100 parts of polyol, 10-20 parts of chain extender, 5-30 parts of cross-linking agent, 1-3 parts of foam stabilizer, 1-2 parts of blowing agent, 1-2 parts of free radical scavenger, 0.2-0.6 parts of catalyst, and 190-210 parts of isocyanate.
[0012] Further, the polyol is one or a mixture of two or more of a multifunctional high hydroxyl value polyether polyol, a difunctional polyester polyol, a tetramethylene ether polyol, a polycaprolactone polyol, a bisphenol A polyoxypropylene ether, and a polycarbonate polyol; the hydroxyl value of the multifunctional high hydroxyl value polyether polyol is preferably 350-550 mgKOH / g, and the hydroxyl value of the difunctional polyester polyol is preferably 150-350 mgKOH / g;
[0013] The chain extender is one or a mixture of two or more of a liquid small molecule diol or a liquid small molecule diol amine;
[0014] The cross-linking agent is a liquid small molecule polyol or a liquid small molecule polyol amine;
[0015] The foam stabilizer is a silicone-polyether copolymer, cellulose, soluble starch, or biopolymer;
[0016] The foaming agent is selected from water, carbon dioxide, azo compounds, nitroso compounds, and sulfonylhydrazide compounds;
[0017] The free radical scavenger is one or a mixture of two or more of propionate compounds, phenolic compounds and phosphite compounds;
[0018] The catalyst is one or a mixture of two or more of organic tin, triethylenediamine, bis(dimethylaminoethyl)ether, cyclohexyl tertiary amine, and dimethylamine;
[0019] The isocyanate is one or a mixture of two or more of polyphenyl polymethylene polyisocyanate, toluene diisocyanate and diphenylmethane diisocyanate.
[0020] Further, the polyol is selected from polyether polyol 4110, polyether polyol DV125 and polyether polyol Mn500;
[0021] The liquid small molecule diol is selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, diethylene glycol, triethylene glycol 1,2-pentanediol, and 1,5-pentanediol;
[0022] The liquid small molecule diol amine is selected from diethanolamine, methyldiethanolamine, and bis(hydroxyisopropyl)aniline;
[0023] The liquid small molecule polyol is selected from propylene glycol and 1,2,6-hexanetriol;
[0024] The liquid small molecule polyol amine is triethanolamine;
[0025] The foam stabilizer is selected from one or a mixture of two or more of foam stabilizer AK8801, AK8805, foam stabilizer AK8818, foam stabilizer B8433, foam stabilizer B8443, foam stabilizer DC-5640, foam stabilizer S-6920, foam stabilizer H330, and foam stabilizer H350;
[0026] In the free radical scavenger, the propionate compound is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], and diethylene thioate bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate];
[0027] The phenolic compound is selected from 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzene)benzene, 1,5-tris(3,5-di-tert-butyl-4-hydroxybenzene)-s-triazine-2,4,6-(1H,3H,5H)trione;
[0028] The phosphite compound is selected from tris(2,4-di-tert-butylphenyl)phosphite and triphenyl phosphite;
[0029] In the catalyst, the organotin is selected from stannous octoate (T9), dibutyltin dilaurate (T12), and dibutyltin bisthiol (T131);
[0030] The triethylenediamine is triethylenediamine;
[0031] The bis(dimethylaminoethyl) ether is bis(dimethylaminoethyl) ether;
[0032] The tertiary cyclohexylamines are selected from dimethylcyclohexylamine and N-methyldicyclohexylamine;
[0033] The dimethylamines are selected from pentamethyldiethylenetriamine and tetramethylethylenediamine.
[0034] Among them, stannous octoate is also known as T9; dibutyltin dilaurate is also known as T12; dibutyltin bisthiol is also known as T131; triethylenediamine is also known as Dabco2040; bis(dimethylaminoethyl) ether is also known as Dabco BL-19; dimethylcyclohexylamine is also known as Polycat 8; N-methyldicyclohexylamine is also known as Polycat 12; pentamethyldiethylenetriamine is also known as Polycat 5; and tetramethylethylenediamine is also known as Toyocat TE.
[0035] Further, the polyol is polyether polyol 4110;
[0036] The foam stabilizer is foam stabilizer S-6920;
[0037] The catalyst is catalyst 2040 .
[0038] The present invention also provides a method for preparing the above-mentioned low-density and high-strength polyurethane foam, characterized in that the method comprises the following steps: weighing polyol, chain extender, cross-linking agent, foam stabilizer, blowing agent, free radical scavenger and catalyst, stirring evenly, then adding isocyanate, continuing to stir evenly, pouring the mixture into a mold, and ripening to obtain the foam.
[0039] Furthermore, the stirring speed of the first stirring is 1000-5000 r / min, and the stirring time is 30-100 seconds; the stirring speed of the second stirring is 1000-5000 r / min, and the stirring time is 5-30 seconds; and the aging is room temperature curing for 16-30 hours.
[0040] Furthermore, the stirring speed of the first stirring is 3000 r / min, and the stirring time is 60 seconds; the stirring speed of the second stirring is 3000 r / min, and the stirring time is 15 to 20 seconds; and the aging is room temperature curing for 24 hours.
[0041] The present invention also provides the use of the polyurethane foam in preparing materials used in the fields of home furnishing, transportation, refrigeration and heat preservation, and building construction.
[0042] Furthermore, the material is a shock-absorbing and cushioning material, a sound-absorbing material, a packaging material, or a structural supporting material.
[0043] In the present invention, polyol refers to a compound containing 3 or more hydroxyl groups; polyol amine refers to a compound containing 3 or more amine groups.
[0044] Beneficial effects achieved by the present invention:
[0045] According to public reports, the correlation coefficient of compression strength of non-composite closed-cell rigid polyurethane foam is in the range of 1.5-2.1, and the correlation coefficient of compression modulus is in the range of 1.6-1.72. The correlation coefficients of the foam made by the preparation method of the present invention are 2.32 and 1.85 respectively. At the same density, the foam made by the preparation method of the present invention has higher strength ((2.32-2.1) / 2.1=0.10) and modulus ((1.85-1.72) / 1.72=0.13), achieving a performance improvement of about 10%.
[0046] In summary, the present invention provides a low-density, high-strength one-step polyurethane foam and its preparation method and use. The polyurethane foam is prepared from the following components in parts by weight: 100 parts of polyol, 5-30 parts of chain extender, 5-30 parts of cross-linking agent, 0.5-5 parts of foam stabilizer, 0.5-4 parts of foaming agent, 0.5-4 parts of free radical scavenger, 0.1-1 parts of catalyst, and 150-300 parts of isocyanate. The present invention obtains a polyurethane foam with excellent comprehensive mechanical properties through a one-step method, and has the advantages of both low density and high strength, and has good application prospects.
[0047] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0048] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. DETAILED DESCRIPTION
[0049] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0050] Polyether polyol 4110 was purchased from Wanhua Chemical (Yantai) Rongwei Polyurethane Co., Ltd.; polyether polyol DV125 was purchased from and polyether polyol Mn500 was purchased from Bluestar Dongda Chemical Co., Ltd.; phthalic anhydride polyester polyol (CAS No.: 32472-85-8) was purchased from Shandong Orilon Chemical Co., Ltd.; polyphenyl polymethylene polyisocyanate (CAS No.: 9016-87-9) was purchased from Wanhua Chemical Group Co., Ltd.; ethylene glycol, propylene glycol, and 1,4-butanediol were purchased from Chengdu Cologne Chemical Co., Ltd.; 1,2-pentanediol and trimethylolpropane were purchased from Shanghai Adamas Reagent Co., Ltd.; foam stabilizer S-6920 was purchased from Shanghai Roca New Materials Co., Ltd.; catalyst 2040 is a commercially available product; pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was purchased from BASF.
[0051] The "room temperature" referred to in the present invention is 25°C.
[0052] Unless otherwise specified, the amounts of raw materials in the examples are expressed in parts by weight.
[0053] Example 1: Preparation of polyurethane foam by one-step method
[0054] First, polyether polyol 4110 was precooled in a refrigerator at 4°C for 24 hours, and 100.43 parts of polyether polyol 4110, 6.02 parts of ethylene glycol, 9 parts of propylene glycol, 2.12 parts of foam stabilizer S-9620, 0.4 parts of catalyst 2040, 1.84 parts of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester free radical scavenger and 1.31 parts of water were added to a foaming cup. The agitator was stirred at a speed of 3000 r / min for 1 minute, and a mixture was obtained after sufficient mixing.
[0055] The isocyanate index is an important indicator for measuring the degree and properties of the reaction of isocyanate or polymer system. Weigh 195.63 parts of polyphenyl polymethylene polyisocyanate with an isocyanate index of 1.05, add the isocyanate to the mixture, and stir at a speed of 3000r / min for 15-20s to ensure full mixing. Finally, pour the mixture into the mold at room temperature to complete the reaction molding process, and then take out the polyurethane foam after further aging at room temperature for 24h.
[0056] Table 1. Raw material ratio of Example 1
[0057]
[0058] Example 2: Preparation of polyurethane foam by one-step method
[0059] The polyurethane foam was prepared by the method of Reference Example 1, except that the raw material ratio of Example 2 was:
[0060] Table 2. Raw material ratio of Example 2
[0061]
[0062] Example 3: Preparation of polyurethane foam by one-step method
[0063] The method of reference embodiment 1 is different only in that the raw material ratio of embodiment 3 is:
[0064] Table 3. Raw material ratio of Example 3
[0065]
[0066]
[0067] Example 4: Preparation of one-step polyurethane foam
[0068] The method of reference embodiment 1 is different only in that the raw material ratio of embodiment 4 is:
[0069] Table 4. Raw material ratio of Example 4
[0070]
[0071] Example 5: Preparation of one-step polyurethane foam
[0072] The method of reference embodiment 1 is different only in that the raw material ratio of embodiment 5 is:
[0073] Table 5. Raw material ratio of Example 5
[0074]
[0075] The following is the preparation method of the comparative samples.
[0076] The method of Reference Example 1 is different only in that the comparative sample is prepared according to the ratio in Table 6.
[0077] Table 6. Comparative samples at different ratios
[0078]
[0079]
[0080] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0081] Experimental Example 1: Mechanical properties test of polyurethane foam under different ratios
[0082] 1. Experimental methods
[0083] (1) Test compressive strength and compressive modulus: Refer to GB 8813-2020 "Determination of compression properties of rigid foam plastics", the sample size is 30mm×30mm×30mm, and the compression rate is 2mm / min. The yield strength is selected as the compressive strength.
[0084] (2) Test flexural strength and flexural modulus: refer to GB8812.2-2007 "Determination of flexural properties of rigid foam plastics", the sample size is 120mm×25mm×20mm, the span is 100mm, and the test speed is 10mm / min. The fracture strength is selected as the flexural strength.
[0085] (3) Impact strength test: Refer to GB / T 1043.1-2008 "Determination of impact properties of plastics" to conduct unnotched simple supported beam impact test. The size of the sample is 120mm×15mm×10mm, the test span is 70mm, the test pendulum is 2J, and the speed is 1mm / s. The fracture strength is selected as the impact strength. Select a sample of 30mm×30mm×30mm, and obtain the dry weight m1 and foam volume v by measurement. Immerse the sample in water and remove bubbles on the surface of the sample with a soft brush or stirring. Weigh again after 24 hours to obtain the wet weight m2. Water absorption rate = (m2-m1) / v.
[0086] (4) Test loss factor: The material was made into a sample of 10 mm × 8 mm × 8 mm, and the loss factor of the polyurethane foam was tested by compression. The test frequency was 1 Hz, the strain was 1%, the test temperature range was -70°C to 180°C, and the heating rate was 5°C / min.
[0087] (5) Test of non-stick time: According to the definition of various foaming reaction characteristic parameters, test conditions and test methods in HG / T 4574-2014 "Determination of foaming reaction characteristics of polyurethane raw materials", non-stick time and other parameters are measured. That is, the time from the start of material mixing to the time when a gloved finger or a glass rod touches the foam surface without sticking.
[0088] 2. Experimental results
[0089] The mechanical properties test results of each group of polyurethane foam are shown in Table 7.
[0090] Table 7. Mechanical properties test results of polyurethane foam at different ratios
[0091]
[0092]
[0093] It can be seen that the density of the polyurethane foams obtained in Examples 1 to 5 of the present invention is 98.07±1.1 to 102±3 kg / m 3 Between, meet the application requirements.
[0094] Compared with Comparative Examples 1-5, the bending strength of the polyurethane foam obtained in the embodiment is significantly improved; compared with Comparative Examples 1, 2, and 3, the bending modulus and impact performance of the polyurethane foam obtained in the embodiment are significantly improved.
[0095] Compared with Comparative Examples 1-5, the compressive strength of the polyurethane foam obtained in the embodiment is significantly improved; compared with Comparative Example 5, the compressive modulus of the polyurethane foam obtained in the embodiment is significantly improved.
[0096] Compared with Comparative Examples 1-5, the 25°C loss factor (room temperature damping factor) of the polyurethane foam obtained in the embodiment is significantly improved, and the cushioning and shock absorbing performance is better; in addition, the 25°C loss factor of the polyurethane foam obtained in the embodiment is higher than that of ordinary low-density rigid polyurethane foam.
[0097] Compared with Comparative Examples 1-5, the non-stick time of the polyurethane foam obtained in the embodiment is significantly improved, and a longer process time and a longer solidification time can be provided. A longer process time is conducive to the material fully filling large and special-shaped mold cavities. A longer solidification time means a gentler reaction, and the reaction heat can be released smoothly over a longer period of time, greatly reducing the risk of heartburn.
[0098] Compared with Comparative Examples 1-5, the water absorption rate of the polyurethane foam obtained in the embodiment is significantly reduced.
[0099] The above results show that the polyurethane foam prepared in the embodiment of the present invention achieves a balance between strength (rigidity) and toughness (flexibility), has excellent comprehensive mechanical properties, and has the advantages of high cushioning and shock absorbing performance, long non-stick time and low water absorption.
[0100] In summary, the present invention provides a low-density, high-strength one-step polyurethane foam and its preparation method and use. The polyurethane foam is prepared from the following components in parts by weight: 100 parts of polyol, 5-30 parts of chain extender, 5-30 parts of cross-linking agent, 0.5-5 parts of foam stabilizer, 0.5-4 parts of foaming agent, 0.5-4 parts of free radical scavenger, 0.1-1 parts of catalyst, and 150-300 parts of isocyanate. The present invention obtains a polyurethane foam with excellent comprehensive mechanical properties through a one-step method, and has the advantages of both low density and high strength, and has good application prospects.
Claims
1. A polyurethane foam, characterized in that The invention is prepared from the following components in parts by weight: 100 parts of polyol, 5-30 parts of chain extender, 5-30 parts of crosslinker, 0.5-5 parts of foam stabilizer, 0.5-4 parts of foaming agent, 0.5-4 parts of free radical scavenger, 0.1-1 parts of catalyst and 150-300 parts of isocyanate.
2. The polyurethane foam according to claim 1, characterized in that The polyurethane foam is prepared from the following components in parts by weight: 100 parts of polyol, 10-20 parts of chain extender, 5-30 parts of crosslinking agent, 1-3 parts of foam stabilizer, 1-2 parts of blowing agent, 1-2 parts of free radical scavenger, 0.2-0.6 parts of catalyst and 190-210 parts of isocyanate.
3. The polyurethane foam according to claim 1, characterized in that The polyol is one or a mixture of two or more of a multifunctional high hydroxyl value polyether polyol, a difunctional polyester polyol, a tetramethylene ether polyol, a polycaprolactone polyol, a bisphenol A polyoxypropylene ether, and a polycarbonate polyol; the hydroxyl value of the multifunctional high hydroxyl value polyether polyol is preferably 350-550 mgKOH / g, and the hydroxyl value of the difunctional polyester polyol is preferably 150-350 mgKOH / g; The chain extender is one or a mixture of two or more of a liquid small molecule diol or a liquid small molecule diol amine; The cross-linking agent is a liquid small molecule polyol or a liquid small molecule polyol amine; The foam stabilizer is a silicone-polyether copolymer, cellulose, soluble starch, or biopolymer; The foaming agent is selected from water, carbon dioxide, azo compounds, nitroso compounds, and sulfonylhydrazide compounds; The free radical scavenger is one or a mixture of two or more of propionate compounds, phenolic compounds, and phosphite compounds; The catalyst is one or a mixture of two or more of organic tin, triethylenediamine, bis(dimethylaminoethyl)ether, cyclohexyl tertiary amine, and dimethylamine; The isocyanate is one or a mixture of two or more of polyphenyl polymethylene polyisocyanate, toluene diisocyanate and diphenylmethane diisocyanate.
4. The polyurethane foam according to claim 3, characterized in that The polyol is selected from polyether polyol 4110, polyether polyol DV125 and polyether polyol Mn500; The liquid small molecule diol is selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, diethylene glycol, triethylene glycol 1,2-pentanediol, and 1,5-pentanediol; The liquid small molecule diol amine is selected from diethanolamine, methyldiethanolamine, and bis(hydroxyisopropyl)aniline; The liquid small molecule polyol is selected from propylene glycol and 1,2,6-hexanetriol; The liquid small molecule polyol amine is triethanolamine; The foam stabilizer is selected from one or a mixture of two or more of foam stabilizer AK8801, AK8805, foam stabilizer AK8818, foam stabilizer B8433, foam stabilizer B8443, foam stabilizer DC-5640, foam stabilizer S-6920, foam stabilizer H330, and foam stabilizer H350; In the free radical scavenger, the propionate compound is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], and diethylene thioate bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]; The phenolic compound is selected from 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzene)benzene, 1,5-tris(3,5-di-tert-butyl-4-hydroxybenzene)-s-triazine-2,4,6-(1H,3H,5H)trione; The phosphite compound is selected from tris(2,4-di-tert-butylphenyl)phosphite and triphenyl phosphite; In the catalyst, the organotin is selected from stannous octoate (T9), dibutyltin dilaurate (T12), and dibutyltin bisthiol (T131); The triethylenediamine is triethylenediamine; The bis(dimethylaminoethyl) ethers are bis(dimethylaminoethyl) ether; The tertiary cyclohexylamines are selected from dimethylcyclohexylamine and N-methyldicyclohexylamine; The dimethylamines are selected from pentamethyldiethylenetriamine and tetramethylethylenediamine.
5. The polyurethane foam according to claim 4, characterized in that The polyol is polyether polyol 4110; The foam stabilizer is foam stabilizer S-6920; The catalyst is catalyst 2040 .
6. A method for preparing the polyurethane foam according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: weighing polyol, chain extender, crosslinking agent, foam stabilizer, foaming agent, free radical scavenger and catalyst, stirring evenly, adding isocyanate, continuing to stir evenly, pouring the mixture into a mold, and ripening to obtain the product.
7. The method according to claim 6, characterized in that The stirring speed of the first stirring is 1000-5000 r / min, and the stirring time is 30-100 seconds; the stirring speed of the second stirring is 1000-5000 r / min, and the stirring time is 5-30 seconds; the aging is room temperature curing for 16-30 hours.
8. The method according to claim 7, characterized in that The stirring speed of the first stirring is 3000 r / min, and the stirring time is 60 seconds; the stirring speed of the second stirring is 3000 r / min, and the stirring time is 15-20 seconds; the aging is room temperature curing for 24 hours.
9. Use of the polyurethane foam according to any one of claims 1 to 5 in preparing materials used in the fields of home furnishing, transportation, refrigeration and thermal insulation, and building construction.
10. The use according to claim 9, characterized in that The materials are shock-absorbing and buffering materials, sound-absorbing materials, packaging materials, and structural supporting materials.
Citation Information
Patent Citations
High-hydrolysis-resistant foaming material of spray polyurethane foaming plastic and preparation method of high-hydrolysis-resistant foaming material
CN106750124A
High-temperature-resistant polyurethane foaming material as well as preparation method and application thereof
CN113292696A
Polyurethane material for building door and window profile, building door and window profile and preparation method of building door and window profile
CN114133528A
Polyol-containing composition, foamable urethane resin composition, and polyurethane foam
JP2023081760A
Cited By
Sound insulation and shock absorption sound insulation cotton and preparation method thereof
CN120248580A